2018
DOI: 10.1177/1178630218812805
|View full text |Cite
|
Sign up to set email alerts
|

The Restorative Value of the Urban Environment: A Systematic Review of the Existing Literature

Abstract: Background:Stress poses a major issue in our modern society, making restoration an important research focus. Restoration likelihood has mostly been observed in nature, which was compared with urban environments that have little restorative potential, eg, industrial areas. However, many people reside in and need to find restoration in cities. The main aim of this review is to summarize research that has focused on investigating restoration possibilities in urban environments and the environmental elements inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 77 publications
5
64
0
2
Order By: Relevance
“…With the growing urban population and the need for good mental health in coping with pressurised modern lifestyles [30], improving restorativeness in contemporary cities becomes an increasingly significant research topic. Previous empirical findings generally show that urban greenspace can provide a liveable, peaceful, and walkable environment that encourages perceived restorativeness [31]. In terms of usage, running in parks or outside towns was found to have a positive association with perceived restorativeness [32].…”
Section: Environmental Qualities and Perceived Restorativeness In Thementioning
confidence: 84%
“…With the growing urban population and the need for good mental health in coping with pressurised modern lifestyles [30], improving restorativeness in contemporary cities becomes an increasingly significant research topic. Previous empirical findings generally show that urban greenspace can provide a liveable, peaceful, and walkable environment that encourages perceived restorativeness [31]. In terms of usage, running in parks or outside towns was found to have a positive association with perceived restorativeness [32].…”
Section: Environmental Qualities and Perceived Restorativeness In Thementioning
confidence: 84%
“…In fact, they were sourced from a stock image database in which rather beautiful and high-quality images are included. Furthermore, we selected urban areas that include not only streetscapes and industrial areas, as for example in Berman et al ( 2008), but also inner city, historic, and residential areas that might be rated as more restorative and beautiful (e.g., Karmanov & Hamel, 2008;Weber & Trojan, 2018). However, note that Study 1 as well as both studies reported in Authors ( 2021) confirmed that our urban images were (explicitly and implicitly) rated as significantly less restorative than the nature images.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of the diversity of urban environments raises the question what characteristics generally lead to the non-positive effects on restoration-related measures (compared to nature stimuli; for a related discussion, see Berto, 2020; Hicks et al, 2020aHicks et al, , 2020b. Similarly, several researchers emphasized considering the diversity of urban environments and showed restorative effects for urban areas as well (Collado & Manrique, 2020;Scopelliti et al, 2019;Staats et al, 2016;Weber & Trojan, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of green areas and public spaces, a neighborhood's traffic conditions and safety, and trust between neighbors have all been found to affect people's depressive moods. A lack of green space has been found to cause depressive mood in several studies [17] and exposure to the natural environment has been found to help relieve depressive moods and reduce stress [50]. Communal space in neighborhood environments has been found to have a positive impact on relieving depressive mood by helping people develop strong social relationships [51].…”
Section: Effect Of Neighborhood Environment On Depressive Moodsmentioning
confidence: 99%